2019
DOI: 10.3389/fimmu.2018.03117
|View full text |Cite
|
Sign up to set email alerts
|

Inducible IFN-γ Expression for MHC-I Upregulation in Devil Facial Tumor Cells

Abstract: Importantly, the techniques are readily transferable for testing gene function in DFT2 cells and other non-traditional species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 37 publications
2
18
0
1
Order By: Relevance
“…The restoration of functional MHC-I molecules without concomitant upregulation of PDL1 and SAHA-UK has multiple advantages over IFNG for triggering effective cytotoxic responses against DFT cells. First, cells transfected with NLRC5 constitutively express MHC-I and therefore do not require culturing in IFNG, which can be problematic as IFNG can also reduce cell viability 17 . Second, PDL1 negatively regulates T cell responses by inducing T cell anergy 73 and apoptosis 74 while limiting T cell activity 75 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The restoration of functional MHC-I molecules without concomitant upregulation of PDL1 and SAHA-UK has multiple advantages over IFNG for triggering effective cytotoxic responses against DFT cells. First, cells transfected with NLRC5 constitutively express MHC-I and therefore do not require culturing in IFNG, which can be problematic as IFNG can also reduce cell viability 17 . Second, PDL1 negatively regulates T cell responses by inducing T cell anergy 73 and apoptosis 74 while limiting T cell activity 75 .…”
Section: Discussionmentioning
confidence: 99%
“…PDL1 and SAHA-UK molecules can be counterproductive to the cell-mediated immune response mediated by MHC-I recognition. Additionally, the inhibition of cell proliferation and increased DFT cell death associated with IFNG 17 constrain large-scale production of IFNG-treated DFT cells for whole cell vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…APCs, such as DCs and macrophages, play a role in the activation of acquired immune response by priming naïve T-cells to extracellular pathogens and tumors [ 3 ]. Interestingly, IFN-γ signaling was shown to be involved in this process by upregulating the expression of MHC I complex on both immune and non-immune cells, therefore facilitating the recognition of pathogen-derived antigens by effector T-cells (Teffs) [ 55 , 56 ]. More specifically, type II interferon increases IRF1 expression, which enhances the expression of MHC class I molecules by binding to the promoter region [ 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, these pathways have received little attention in transmissible cancers and other naturally occurring cancers in nonmodel species ( Fig. 1 and table S1) (17)(18)(19). We have previously shown that the inhibitory immune checkpoint molecule programmed death ligand 1 (PDL1) is expressed in the DFT microenvironment and is up-regulated by interferon- (IFN-) in vitro (17).…”
Section: Introductionmentioning
confidence: 99%